The wounded warrior handbook a resource guide for returning veterans - Moore, Janelle 1972-; Lawhorne, Cheryl 1968-; Philpott, Don 1946- (2015)
The typical wounded soldier must complete and file twenty-two forms after an active-duty injury. To soldiers and their families coping with the shock and reality of the injuries, figuring out what to do next--even completing tasks that seem easy like submitting paperwork--can be overwhelming and confusing. The second edition of this popular resource guide has been thoroughly revised to reflect new policies, additional benefits, updated procedures, and changes to insurance, including traumatic injury insurance and social security disability insurance. New chapters cover veterans' benefits in depth--which have seen significant changes in the last two years--and returning to active duty after an injury.As in the previous edition, this guide directs you to answers and resources for the most pressing and difficult questions that wounded veterans face, such as: Where can I find information on symptoms and treatments of injuries? How do I get through all this paperwork? Where can I get legal assistance? What can I do for employment? How do I get back into everyday life? How can I return to active duty? How do I deal with insurance? What benefits are available to me, and how do I claim them? What about my family? How can they help me? This trusted resource is both comprehensive and easy to use, and now the most up-to-date guide for wounded veterans and their families dealing with active-duty injuries.